Eye-Movements During Navigation in a Virtual Environment: Sex Differences and Relationship to Sex Hormones - Harris, TiAnni; Hagg, Johanna; Pletzer, Belinda (Frontiers in Neuroscience, 2022)
Sex differences in spatial navigation have been related to different navigation strategies. For example, women are more likely to utilize local landmark-information in the environment compared to men. Furthermore, sex differences appear to be more pronounced when distances need to be judged in Euclidian terms and an allocentric representation of the environment is necessary. This suggests differential attentional processes during spatial navigation in men and women. However, eye-tracking studies on spatial navigation exploring these attentional processes are rare. The present study (39 men and 36 women) set out to investigate sex differences in eye-movements during spatial navigation in a 3D environment using virtual reality googles. While we observed the expected sex differences in overall navigation performance, women did not benefit from the landmark-based instruction. Gaze fixations were in accordance with the preferred Euclidian strategy in men, but did not confirm the expected landmark-based strategy in women. However, high estradiol levels where related to an increased focus on landmark information. Surprisingly, women showed longer gaze distances than men, although the utilization of distal landmarks has been related to allocentric representations preferred by men. In fact, larger gaze distances related to slower navigation, even though previous studies suggest that the utilization of distal landmarks is beneficial for navigation. The findings are discussed with respect to the utility of virtual reality presentation for studies on sex differences in navigation. While virtual reality allows a full first-person immersion in the environment, proprioceptive and vestibular information is lacking.